Design and Development of an Integrated Control System for the Pasteurization Division and Flavoring Tanks in Milk Production to Support Vocational Education and Industry University Collaboration - Prahesti, Fidya Eka; Indrawati, Elsanda Merita; Suwardono, Agus; Setyawan, Dodi; Nurrohim, Muhammad Danu (DPTE FT UNY, 2026)
The dairy processing industry in Indonesia continues to grow with a consumption increase of 5–7% per year, yet more than 70% of the national milk demand is still met through imports. This situation calls for an enhancement of production capacity and human resource competencies, particularly vocational graduates who are considered to lack practical skills that meet industry needs. This study aims to design an integrated control system in the pasteurization division and flavor tank as a learning tool as well as a prototype for industry–university collaboration. The methods used include a literature review of pasteurization process standards, design of hardware and software for a sensor- and microcontroller-based control system, implementation of a laboratory prototype, and performance testing based on parameters of temperature, time, and product homogeneity. The research results indicate that the control system can maintain pasteurization temperatures in the range of 72–75°C with a deviation of ±1°C, and the flavor mixing process remains stable and homogeneous. The integration of the two divisions allows for the simulation of production processes that resemble actual industrial conditions. The resulting practicum module enhances students' understanding of process control and industrial automation concepts. Initial evaluations show a 35% improvement in students' practical skills compared to conventional methods. This prototype has the potential to become a project-based learning model relevant to the needs of the food industry.